2000
DOI: 10.1136/fn.82.1.f64
|View full text |Cite
|
Sign up to set email alerts
|

Six years' experience of prophylactic oral vitamin K

Abstract: Aims-The ability of oral vitamin K to eliminate all risk of vitamin K deficiency bleeding during the first three months of life was studied. Methods-Babies (n=182 000) in the north of England judged well enough to be oVered milk within 12 hours of birth were given 1 mg of phytomenadione (vitamin K 1 ) suspended in a medium chain triglyceride oil by mouth at delivery between 1993 and 1998. The parents of those who were breastfed were given a further three doses to give to the baby once every two weeks after dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…3,9,15 The method presented here, comparison of well-delineated and homogeneous risk populations, may be very helpful in this respect. In contrast to nationwide surveillance studies, which are sensitive to underreporting, 3,12 it seems to be a reliable method to detect prophylactic failures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3,9,15 The method presented here, comparison of well-delineated and homogeneous risk populations, may be very helpful in this respect. In contrast to nationwide surveillance studies, which are sensitive to underreporting, 3,12 it seems to be a reliable method to detect prophylactic failures.…”
Section: Discussionmentioning
confidence: 97%
“…[12][13][14] However, prophylactic failures have continued to occur, mostly in infants who later proved to have a cholestatic liver disease. 3,9,[15][16][17][18] Cholestatic infants are especially sensitive to suboptimal vitamin K availability, because the absence of intestinal bile greatly reduces the absorption of vitamin K and other fat-soluble vitamins. 19,20 The repeated occurrence of prophylactic failures in infants with unrecognized cholestatic liver disease warrants careful evaluation of the efficacy of vitamin K prophylactic regimens in these infants.…”
Section: What This Study Addsmentioning
confidence: 99%
“…route is known to be effective in preventing both early haemorrhagic disease in neonates and late-onset bleeding in older babies (Dam et al, 1952;McNinch and Tripp, 1991;Zipursky, 1999). The efficacy of oral vitamin K is less certain as there is a recognised problem of absorption in some babies, and additional difficulties in compliance with multiple-dose oral regimens (Zipursky, 1999;Wariyar et al, 2000;von Kries et al, 2003).…”
mentioning
confidence: 99%
“…There were 22 cases of α1-antitrypsin deficiency, 11 biliary atresia and 22 other liver diseases. Wariyar et al reported four cases of late VKDB among 182,000 babies with oral vitamin K prophylaxis [7]. Two had undiagnosed α1-antitrypsin deficiency.…”
Section: Discussionmentioning
confidence: 98%